Study of fetomaternal outcome in various modes of breech delivery in a tertiary care hospital- MGM GH, Trichy - Mohanraj, Uma; Adhirai, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Aim of the study was to optimize the fetomaternal outcome using different modes of delivery in breech presentation and objective of the study was to optimize the maternal and perinatal outcome in various modes of breech delivery. Methods: Among 150 mothers with different parity and gestational age having singleton breech were studied during May 2019- October 2019 for the period of 6 months at KAPV government medical college. Fetomaternal outcome was compared in various modes of breech delivery during this study period in our institute. This study was a prospective analytical study. Results: Incidence of breech presentation was 3.3% of total deliveries in this institute. Around 4 (26.6%) cases by emergency LSCS, 48 (32%) cases delivered vaginally, 62 (41.3%) cases by elective LSCS. Comparatively, large number of cases were delivered by planned caesarean section in our institute. The maternal and perinatal morbidity and mortality was found to be less in planned caesarean section compared with other modes of delivery in this study. Conclusions: In view of insignificant difference in the fetomaternal outcome balanced decision about mode of delivery on a case by case basis will go a long way in improving both fetal and maternal outcome. Regular drills and conduct of assisted vaginal breech delivery should be pursued in all maternity hospitals.